ANALISIS YURIDIS ATAS HAK DAN KEWAJIBAN PARA PIHAK DALAM PERJANJIAN ANTARA DRIVER/PEMILIK KENDARAAN DENGAN PERUSAHAAN PENYEDIA JASA APLIKASI TRANSPORTASI ONLINE - BANI AFFAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Jelly Leviza, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Dedi Harianto, SH, MHumOnline application based-transportation service needs technology in facilitating people’s mobility. One of the ojek service providers that uses android application technology is PT. GO JEK in which ojek application can be downloaded through smartphone, either android or iOS. The research used juridical empirical and juridical sociological method. It also used descriptive analytic method which described the research object by using samples and data and making general conclusion. The data consisted of primary and secondary data. Secondary data were obtained from primary, secondary, and tertiary legal materials by conducting library research and interviews. The result of the research shows that the legal correlation between driver as the owner of the vehicle and GO JEK makes cooperative contract in the form of partnership, in a written form, underhandedly, in an electronic contract according to UUITE. The settlement is usually done through mediation and negotiation by involving the authorities, Pemprovsu (the North Sumatera Provincial Administration) and Kemenhub (the Ministry of Transportation).Keywords: Transportation, Online, Contract, Partnership